Development of Comic Media Based on Pancasila Student Profiles on the Dimensions of Faith, Piety, and Noble Character in Elementary School - Asmauna, Canika Nur; Rahmi, Laili (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This research aims to develop comic media based on Pancasila student profiles with dimensions of faith, piety, and noble character. The development model used is the ADDIE model, namely analysis, design, and development. This research is development research using qualitative and quantitative approaches and the ADDIE model. The data used in this research comes from expert suggestions and comments in qualitative analysis, while in quantitative analysis, scores obtained from experts and students are used. This research was conducted at SDN 169 Pekanbaru, with a focus on implementing the Pancasila student profile of the dimensions of faith, piety, and noble character as part of the independent learning curriculum. The data sources in this research are teachers, students, validators, material experts, language experts, and design experts. Data collection was carried out through interviews with the principal of SDN 169 Pekanbaru, observations of student character, and analysis of documents related to the implementation of the independent learning curriculum and the profile of Pancasila students at the school. Qualitative data analysis techniques were carried out using the thematic analysis method. Meanwhile, for quantitative data analysis using descriptive statistical methods, this research produces comic media based on Pancasila student profiles with dimensions of faith, piety, and noble character. The development of this comic media involves the use of Figma and Microsoft Word applications, from creating script sketches and adding color to adding effects to comic scenes. The validity of comic media was declared very valid without revision based on the validation results of material experts, language experts, and design experts, with an overall validity percentage reaching 98.21%. Student responses to this comic media were also positive, with an average of 91.03%. Thus, this comic media is suitable for use as a Pancasila-based character learning tool in elementary schools.